PEMAHAMAN DINAMIKA STUDI CERITA RAKYAT DALAM KERANGKA NILAI-NILAI KEMUHAMMADIYAHAN: LITERATUR REVIEW - Nikmah Sari Hasibuan; Moh Nurhakim; Syaiful Amin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2024)
This research examines the understanding of folklore studies within the framework ofMuhammadiyah values using a literature review approach. Through the analysis of ten relatedarticles, this study explores the relationship between folklore and Islamic values, especially in thecontext of Al-Islam Kemuhammadiyahan Education. The research results highlight the diversityof Muhammadiyah values reflected in folklore, including moral values, faith and religiouseducation. In the context of character education, folklore is identified as an effective means ofstrengthening the morality and character of individuals and society. In addition, this researchshows a positive relationship between Muhammadiyah values and Learning Theory andCharacter Education, with the application of learning models that support the development ofstudent creativity and involvement. Students' positive responses to folklore learning show therelevance of this study and strengthening Muhammadiyah values in the educational context. Theresults of this literature show that folklore is not just entertainment, but also has great potentialas a medium for character and moral education that is in line with the values of Al-Islam andKemuhammadiyahan.